Scaling predictions for radii of weakly bound triatomic molecules - Yamashita, Marcelo Takeshi [UNESP]; Marques de Carvalho, R. S. [UNESP]; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 2003)
The mean-square radii of the triatomic molecules 4He 3, 4He 2- 6Li, 4He 2- 7Li, and 4He 2- 23Na were calculated using a renormalized three-body model with a pairwise Dirac-δ interaction, having as physical inputs only the values of the binding energies of the diatomic and triatomic molecules. Molecular three-body systems with bound subsystems were considered. The resultant data were analyzed in detail.
Keywords: Binding energy; Crystal atomic structure; Dimers; Mathematical models; Parameter estimation; Quantum theory; Atomic traps; Root mean square distance; Triatomic molecules; Universal scaling function; Molecular physics